Turkey-Russia partnership in the war over Nagorno-Karabakh : militarised peacebuilding with implications for conflict transformation - Isachenko, Daria (2020)
Zusammenfassung: By siding with Azerbaijan in the conflict over Nagorno-Karabakh, Turkey is primarily pursuing the goal of undermining the current status quo of the region. Ankara aims above all to secure a place at the table where a solution to the conflict between Armenia and Azerbaijan will be negotiated in the future. The Syrian scenario should serve as an example. Turkey thus wants to negotiate with Russia in the South Caucasus, preferably without Western actors. Ankara’s plans are not uninteresting for Moscow. However, because of the complexity of Turkish-Armenian relations, there is a risk that Armenia and Turkey might become the eventual opponents in this conflict, rather than Armenia and Azerbaijan. The EU’s engagement should not be determined by its tense relationship with Turkey, but rather by the UN Security Council resolutions on Nagorno-Karabakh